MEMBUAT ATAU MERANCANG? - Lestari, Ayu Putu Utari Parthami; Witari, Made Ratna; Silantara, I Gede Gandhi (Jurnal Teknik Gradien, 2024)
Understanding the terms making and designing has long been a hot topic of discussion. Tim Ingold said they had influenced understanding and practice in anthropology, archaeology, art, and architecture. The main focus of this paper is to examine how Ingold connects the process of “making” with environmental adaptation and material influences. This research utilizes a literature review of Ingold's major works, especially Making: Anthropology, Archaeology, Art, and Architecture (2019), and compares it with other theories that emphasize the concept of design in the context of modern design. Ingold argues that “making” is a creative process that involves a direct and dynamic interaction with materials and the environment, the outcome of which develops through human engagement with the physical environment. In contrast, “designing” in modern design focuses more on planning, precision, and efficiency, with the process structured before making even begins. Ingold's critique of modern design invites designers, especially architects, to refocus on direct engagement with materials and the environment. This making approach offers new insights for a more adaptive modern design practice, especially in green architecture and community-based design.